Effective dispersal and genetic structure of a small mammal in an intensively managed agricultural landscape: is there any barrier to movement? - Chiappero, Marina B. (2021)
Fil: Chiappero, Marina. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Diversidad y Ecología Animal; Argentina.